Shadow students in Georgia: A Kantian condemnation. Issue 6 (13th December 2021) - Fahmy, Melissa Seymour
Abstract: Millions of immigrants reside in the United States without legal authorisation to do so. This paper examines the educational opportunities available to those brought to the country illegally as children. While the 1982 landmark Supreme Court decision in Plyler v. Doe protects access to K–12 education, in the past 25 years, legislation passed at the federal and state levels has made undocumented persons ineligible for postsecondary education benefits such as federal student loans and in‐state tuition rates. This paper assesses postsecondary education policies in Georgia through the lens of Immanuel Kant's practical philosophy. Utilising Kant's formula of humanity and drawing on the work of Thomas E. Hill, I argue that because these policies cannot be justified from the impartial perspective, they fail to treat undocumented students as ends in themselves and are thus morally unacceptable. Insofar as educational opportunities directly impact our ability to set ends and live as self‐directing, autonomous persons, these restrictions are deeply troubling from a Kantian perspective.